Retrospective analysis of neonatal hydrocephalus over the past 12 years - Chunling Huang; Yunfeng Liu; Tongyan Han; Yuan Wei; Xunke Gu; Rui Li (BMC Pediatrics)
Abstract Background Neonatal hydrocephalus is a serious neurological disease; however, advancements in neonatal care and the increasing survival rate of extremely preterm infants and its incidence, etiology, diagnosis and management have also undergone significant changes. In this study, we aimed to summarize the above clinical changes in neonatal hydrocephalus at our hospital over the past 12 years to provide a reference for clinical practice. Methods This was a single-center retrospective study. To comprehensively collect data on neonatal hydrocephalus, we conducted a case search among hospitalized patients in both the obstetrics and pediatrics departments from January 1, 2010, to December 31, 2021. In the comparative analysis, the infants were divided according to the time of admission into a group for the first 6 years and one for the second 6 years. Between-group comparisons of gestational age, birth weight, etiology, treatment, and prognosis were performed. Results Sixty-two patients (28 in the first 6 years; 34 in the latter 6 years) were diagnosed with neonatal hydrocephalus. Their gestational ages ranged from 25 to 39+6 weeks (median, 30 weeks), and their birth weights ranged from 600 to 4046 g (median, 1255 g). The gestational age and birth weight were significantly lower in the second 6-year group than in the first 6-year group. Furthermore, there was a significant increase in severe germinal matrix-intraventricular hemorrhage (GMH-IVH) in infants and cerebral parenchymal hemorrhage in the latter 6-year group. In terms of surgical treatment, there are more applications of ventricular access devices (VADs) in the latter 6-year group. Among the 62 infants, 21 (33.9%) died, with the majority of deaths (19/21, 90.5%) attributed to treatment withdrawal. Of the surviving infants, 22 had normal development, and 19 had developmental delay. Conclusion Gestational age and birth weight were significantly lower in the second 6-year group than in the first 6-year group, and there was a significant increase in severe intracranial hemorrhage and cerebral parenchymal hemorrhage in this group.